2012
DOI: 10.3133/sir20125037
|View full text |Cite
|
Sign up to set email alerts
|

<i>Escherichia coli</i> bacteria density in relation to turbidity, streamflow characteristics, and season in the Chattahoochee River near Atlanta, Georgia, October 2000 through September 2008&mdash;Description, statistical analysis, and predictive modeling

Abstract: Scatterplot matrix with data histograms and Spearman rank correlation coefficients for base 10 logarithm transformations of Escherichia coli bacteria densities, streamflow, water temperature, and turbidity in water samples collected from the Chattahoochee River near Norcross, Georgia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 18 publications
3
36
0
Order By: Relevance
“…The approach to developing relations between measured bacteria concentration, turbidity, and other available stream data is similar to that used in studies done by USGS for streams in Wisconsin, Kansas, and Georgia, as documented by Baldwin and others (2012), Christensen and others (2000), and Lawrence (2012) and for beaches on the Great Lakes (Francy and others, 2013). Linear regressions are used to relate point measurements of fecal bacteria to instantaneous water-quality values or other data collected on a real-time continuous basis; the resulting regression equations can be used to estimate realtime continuous bacteria concentrations using the real-time continuous data.…”
Section: Development Of Regression Models To Estimate Fecal Coliform mentioning
confidence: 94%
See 1 more Smart Citation
“…The approach to developing relations between measured bacteria concentration, turbidity, and other available stream data is similar to that used in studies done by USGS for streams in Wisconsin, Kansas, and Georgia, as documented by Baldwin and others (2012), Christensen and others (2000), and Lawrence (2012) and for beaches on the Great Lakes (Francy and others, 2013). Linear regressions are used to relate point measurements of fecal bacteria to instantaneous water-quality values or other data collected on a real-time continuous basis; the resulting regression equations can be used to estimate realtime continuous bacteria concentrations using the real-time continuous data.…”
Section: Development Of Regression Models To Estimate Fecal Coliform mentioning
confidence: 94%
“…Near real-time estimates of FIB concentrations can be used to improve protection of human health from exposure to potential pathogens during recreational use of surface waters. Regression equations that incorporate turbidity as a variable have been used to estimate bacteria concentrations for beaches along Lake Erie (Francy and others, 2013;Zimmerman, 2008) and in streams in Kansas (Rasmussen and Ziegler, 2003) and Georgia (Lawrence, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some people in Pasuruan still use river as open defecation area. In United States, Lawrence [21] was monitoring river pollution and found that the new set data estimated using regression-6 on the new Norcross data and regression-12 on the new Atlanta data. It was collected between October 1, 2008 and September 9, 2009.…”
Section: Possibility Of River Watersheed Contaminationmentioning
confidence: 99%
“…During flooding, sediment-associated bacteria are suspended into the water column, elevating E. coli concentrations in the flow. E. coli adsorption to fine sediments and increasing relation to suspended sediment is well documented and generally explained or modeled using measurements of turbidity as a proxy for suspended sediment, because of ease and low-cost of collection (Pandey and Soupir, 2014;Murphy and others, 2016;Lawrence, 2012;Rasmussen and others, 2008;Rasmussen and others, 2005). The fate of E. coli in surface-water systems is governed by multiple physical, chemical, and biological factors.…”
Section: Hydrologic Characterization Of E Coli and Suspended Sedimentmentioning
confidence: 99%